Pulmonary rehabilitation for patients with coronavirus disease 2019 (COVID-19) (2020)
As a highly infectious respiratory tract disease, coronavirus disease 2019 (COVID-19) can cause respiratory, physical, and psychological dysfunction in patients. Therefore, pulmonary rehabilitation is crucial for both admitted and discharged patients of COVID-19. In this study, based on the newly released pulmonary rehabilitation guidelines for patients with COVID-19, as well as evidence from the pulmonary rehabilitation of patients with severe acute respiratory syndrome, we investigated pulmonary rehabilitation for patients with COVID-19 having complications, such as chronic pulmonary disease, and established an intelligent respiratory rehabilitation model for these patients